PENGARUH PROGRAM KAMPUS MENGAJAR DAN SOCIAL INFLUENCE TERHADAP MINAT MENJADI GURU MELALUI INTERNAL LOCUS OF CONTROL SEBAGAI VARIABEL INTERVENING - Himatul Aliyah, Nova; Dwijayanti, Renny (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
The low level of interest among education students in pursuing a teaching career persists, even after gaining field experience through the Kampus Mengajar program. This study aims to analyze the influence of the Kampus Mengajar program and social influence on the interest in becoming a teacher, with internal locus of control as an intervening variable. This research is quantitative in nature and uses path analysis with SPSS version 25 software, involving 135 students from the Faculty of Economics and Business at Universitas Negeri Surabaya who participated in the 7th batch of the Kampus Mengajar program. The results show that both the Kampus Mengajar program and social influence have a positive and significant effect on internal locus of control. Additionally, both variables also directly influence students’ interest in becoming teachers. However, internal locus of control does not have a significant effect on the interest in becoming a teacher, nor does it mediate the influence of the Kampus Mengajar program and social influence on that interest. These findings suggest that direct teaching experience and social influence play an important role in fostering interest in the teaching profession, whereas internal self-control alone is not a sufficiently strong mediating factor. This research is expected to contribute to educational policy development, particularly in shaping the character and readiness of prospective educators.